Droit des relations de travail en Amérique du Nord - Verge, Pierre (Relations industrielles / Industrial Relations, 2001)
The article reviews the book,. "Droit des relations de travail en Amérique du Nord," by Kevin Banks, Lance Compa, Leoncio Lara and Sandra Polaski.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z